Playing Past Racial Silence - MICHAEL DOMÍNGUEZ; ALICE DOMÍNGUEZ (University of Oklahoma Libraries, 2021)
Too often, classroom conversations and literature choices frame race in homogenizing terms, equating racial identity solely with the experience of marginalization. This can have a chilling effect on students whose cultural context has made race an inaccessible topic, positioning conversations about racial identity beyond their zone of proximal development. Leveraging reflections from student-athletes and an analysis of three YA texts, the authors argue that sports-centered YA literature, by normalizing depictions of race, might be leveraged to serve as a critical entry point for robust classroom conversations about the complexity of racial identity, adding nuance and accessibility to a taboo subject.